Wettability and contact angle affect precorneal retention and pharmacodynamic behavior of microspheres - Hanyu Liu; Xinyue Han; Huamei Li; Qi Tao; Jie Hu; Shuo Liu; Huaixin Liu; Jun Zhou; Wei Li; Fan Yang; Qineng Ping; Shijie Wei; et al. (Taylor & Francis Group, 2021)
In the present study, we describe the development of betaxolol hydrochloride and montmorillonite with ion exchange in a single formulation to create a novel micro-interactive dual-functioning sustained-release delivery system (MIDFDS) for the treatment of glaucoma. Betaxolol hydrochloride molecule was loaded onto the montmorillonite by ion exchange and MIDFDS formation was confirmed by XPS data. MIDFDS showed similar physicochemical properties to those of Betoptic, such as particle size, pH, osmotic pressure, and rheological properties. Nevertheless, the microdialysis and intraocular pressure test revealed better in vivo performance of MIDFDS, such as pharmacokinetics and pharmacodynamics. With regards to wettability, MIDFDS had a larger contact angle (54.66 ± 5.35°) than Betoptic (36.68 ± 1.77°), enabling the MIDFDS (2.93 s) to spread slower on the cornea than Betoptic (2.50 s). Moderate spreading behavior and oppositely charged electrostatic micro-interactions had a comprehensive influence on micro-interactions with the tear film residue, resulting in a longer precorneal retention time. Furthermore, MIDFDS had a significant sustained-release effect, with complete release near the cornea. The dual-functioning sustained-release carrier together with prolonged pre-corneal retention time (80 min) provided sufficiently high drug concentrations in the aqueous humor to achieve a more stable and long-term IOP reduction for 10 h. In addition, cytotoxicity and hemolysis tests showed that MIDFDS had better biocompatibility than Betoptic. The dual-functioning microspheres presented in this study provide the possibility for improved compliance due to low cytotoxicity and hemolysis, which suggests promising clinical implications.